Problems of Learning and Teaching Pali and Sanskrit in Mahamakut Buddhist University Nakhon Phathom Province - Sinak, Sanit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The research entitled “Problems of Learning and Teaching Pali and Sanskrit in Mahamakut Buddhist University, Nakhon Pathom Province” was of objectives, namely, 1) to study factors associated with the problems of learning and teaching Pali and Sanskrit including the efficiency of teaching, techniques and methods of teaching, teaching technology and achievements of teaching; 2) to study factors associated with the problems of learning and teaching Pali and Sanskrit; and 3) to suggest solutions of the problems of learning Pali and Sanskrit of students and teaching Pali and Sanskrit of lecturers. The purposive sampling method was used. The tool of data collection was a questionnaire. The statistics used for analyzing data included an Independent Samples t-test, F-test. Findings were as follows: 1) From the analysis of the personal factors, it was found that the majority of respondents were students with below 20 years of age. 2) The factors associated with the problems of learning and teaching Pali and Sanskrit, on the whole, were in the moderate level. When considering for each aspect, it was found that the teaching efficiency and teaching achievements were in the moderate level and teaching techniques and methods and use of teaching technology were also in the moderate level. 3) On the whole, the Pali and Sanskrit teaching problems of the lecturers were in the average level. When considering for each aspect, it was revealed that the problem of their punctuality came first, problem of their readiness in Pali and Sanskrit came second, and their problems of Pali and Sanskrit teaching with direct method came third. 4) From the comparative study of the problems of learning and teaching Pali and Sanskrit it was found that the respondents with different status had a significantly different opinions on the problems of learning and teaching Pali and Sanskrit at 0.05 level. The respondents with different qualifications, and campuses had no different opinions on the problems of learning-teaching Pali and Sanskrit.